2010
DOI: 10.1213/ane.0b013e3181d2ad07
|View full text |Cite
|
Sign up to set email alerts
|

Do Intraoperative Analgesics Influence Breast Cancer Recurrence After Mastectomy? A Retrospective Analysis

Abstract: This retrospective analysis suggests that intraoperative administration of ketorolac decreases the risk of breast cancer relapse compared with other analgesícs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
158
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(173 citation statements)
references
References 17 publications
11
158
2
2
Order By: Relevance
“…In June 2010, Forget et al reported data from a retrospective disease free survival study of 327 consecutive patients comparing various perioperative analgesics and anesthetics (sufentanil, clonidine, ketorolac, and ketamine) in one Belgian hospital and one surgeon [3].…”
Section: Methodsmentioning
confidence: 99%
“…In June 2010, Forget et al reported data from a retrospective disease free survival study of 327 consecutive patients comparing various perioperative analgesics and anesthetics (sufentanil, clonidine, ketorolac, and ketamine) in one Belgian hospital and one surgeon [3].…”
Section: Methodsmentioning
confidence: 99%
“…65 A retrospective review of breast cancer patients undergoing mastectomy suggested that intraoperative ketorolac use was associated with decreased cancer recurrence. 66 Impact of anesthesia for cancer surgery 1253 RCT -randomized controlled trial. GA = general anesthesia; LA = local analgesia; TIVA = total intravenous anesthesia Impact of anesthesia for cancer surgery 1255…”
Section: Agents and Techniques Directly Implicated In Immunosuppressimentioning
confidence: 99%
“…65 Une étude rétrospective chez des patientes ayant un cancer du sein subissant une mastectomie a suggéré que l'utilisation peropératoire de kétorolac était associée à un taux de récidive moindre du cancer. 66 …”
Section: Molécules Et Techniques Directement Impliquées Dans L'immunounclassified
“…The published studies indicate that the anesthetics could directly inhibit immune function of patients, which is closely related with tumor recurrence (1). Aside from the inhibition of anesthetics on lymphocytes, some reports also suggested that anesthetics had a capability to inhibit growth of tumor cells (2)(3)(4).…”
mentioning
confidence: 99%